2019
DOI: 10.1016/j.prro.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Low-Dose Cranial Boost on the Long-Term Outcomes of Adult Patients with High-Risk Acute Lymphoblastic Leukemia Undergoing Total Body Irradiation and Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: Purpose: Total body irradiation (TBI) is an integral part of the conditioning regimen for patients with acute lymphoblastic leukemia (ALL) undergoing allogeneic, hematopoietic, cell transplantation (allo-HCT). There are conflicting data in the literature regarding the utility of a cranial irradiation boost in high-risk adult ALL without evidence of preexisting central nervous system (CNS) involvement. This study investigates the posttransplant clinical outcomes of patients with high-risk adult ALL undergoing T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The OS rates at 10 years did not differ significantly. The annual rates of non-CNS relapses were 17% lower in the methotrexate group (P=0.02), while the CNS and isolated CNS rates were both non significantly lower in this group (244)(245)(246)(247)(248)(249).…”
Section: Therapeutic Option For Cns Leukemiamentioning
confidence: 73%
“…The OS rates at 10 years did not differ significantly. The annual rates of non-CNS relapses were 17% lower in the methotrexate group (P=0.02), while the CNS and isolated CNS rates were both non significantly lower in this group (244)(245)(246)(247)(248)(249).…”
Section: Therapeutic Option For Cns Leukemiamentioning
confidence: 73%
“…20 As such, a lower radiation dose CB may be recommended in cases where such preventive therapies are administered in conjunction with other effective systemic treatments or for those patients at significant risk of CNS leukemia. The studies by Famoso and Su et al 11,12 reported a CB of a low dose, 6 Gy in three fractions, resulting in a total dose of 18 Gy to the entire brain, a lower total dose than that traditionally used for whole brain ALL treatment. Su et al, noted one incident of late cataract formation attributed to radiotherapy, but no neurocognitive toxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Famoso et al showed a significant improvement in 7-year CNS relapse-free survival (100% vs. 76.4%) in high-risk adult ALL patients undergoing TBI conditioning for SCT who received a CB. 11 Su et al evaluated 55 adults with high-risk ALL treated with or without a CB and found an overall CNS failure rate of 2.8% in the CB group and 10.5% in the non-CB group. 12 A recent study by Gao et al demonstrated the efficacy of a pretransplant CB as part of TBI in reducing the risk of CNS relapse.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study from the University of Arizona evaluated 58 patients with high-risk ALL, none of whom had CNS disease at diagnosis, who underwent an allogeneic HSCT using a uniform myeloablative TBI-based conditioning regimen (12 Gy/6 fractions). 11 All patients received prophylactic IT chemotherapy in addition to systemic therapy. A low-dose (6 Gy) cranial boost was associated with improved CNS-relapse free survival at 7 years (100% vs 76%, P = .04), but this did not translate to improved PFS or OS, likely because most patients (4/6) who relapsed in the CNS had a simultaneous marrow failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, there remains some uncertainty whether additional RT to the CNS axis is beneficial in patients without known CNS involvement, and there is wide practice variation regarding RT recommendations in patients with known CNS disease, including field size (CrI vs CSI) and dose. 10 , 11 , 12 …”
Section: Introductionmentioning
confidence: 99%